Tantangan Widyaiswara Badiklat Kemhan dalam Menghadapi Transformasi Badiklat Kemhan menjadi BPSDM Pertahanan di Era VUCA - Juwita (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2024)
The transformation of the Ministry of Defense Training Institute into the Defense BPSDM presents new challenges for widyaiswara who serve as teachers and facilitators in HR development within the Ministry of Defense. This transformation process occurs in the context of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era, where rapid change, uncertainty, complexity, and ambiguity are the main challenges for Widyaiswara Badiklat Kemhan. This research aims to discuss and analyze the challenges faced by Widyaiswara Badiklat Kemhan in facing the transformation of Badiklat Kemhan into BPSDM Pertahanan in the VUCA era. The writing method uses a descriptive qualitative method, namely research conducted to describe, describe a phenomenon that occurs today. The results showed that the change in organizational structure from the Ministry of Defense Training Institute to the Defense BPSDM in the VUCA era (Volatility, Uncertainty, Complexity, Ambiguity) was a strategic step, therefore the widyaiswara improved themselves by attending the required training so that they could master applications such as Moodle, Google Classroom, Zoom, and other platforms and software for content creation, such as Adobe Captivate, Camtasia, Canva, or Articulate Storyline and have skills in creating interesting and informative digital content, both in the form of video tutorials, digital modules, and infographics are key in optimizing the role of widyaiswara.